Structure and Electronic Properties of Transition Metal Doped Kaolinite Nanoclay - Liangjie Fu; Huaming Yang (Nanoscale Research Letters, 2017)
Abstract In this work, a series of transition metal (Cr, Mn, Fe, and Co) doped kaolinite nanoclays were investigated by density functional theory (DFT) calculations. The influence of metal doping on geometric structure and electronic structure of kaolinite was analyzed. The ferromagnetic (FM), antiferromagnetic (AFM), and nonmagnetic (NM) states of transition metal (TM) doped kaolinite structures were studied. The crystal volume, lattice parameters, bond length, charge, and spin were calculated by dispersion-corrected density functional theory (DFT-D2). The results indicated that Cr3+ and Fe3+ dopants showed more stable under AFM state, while Mn3+ preferred both AFM and FM states, and Co3+ dopant preferred NM state. Also, the transition metal doping could induce lattice volume expansion and some dopant states in the band gap.